An Evaluation of the effect of macroeconomic factors on the returns of the real estate market in Nairobi - Gichuru, Alex Mwangi (Strathmore University, 2022)
Kenya's real estate sector has undergone a boom that began in the mid to late 2000s as the property market adapted to growing demand. Nairobi was named the fastest-growing real estate market in the world by real estate management firm Knight Frank in its 2012 Wealth Report, outperforming cities like Miami. Since 2000, property values have climbed 4.44 times. The real estate sector is pivotal to the development of any home nation. Property prices, in specific, are affected by changes in macroeconomic variables for example GDP, interest rates, inflation, money supply and unemployment. Kenya's real estate market is growing swiftly in comparison to other African emerging countries, despite high inflation, high unemployment, high interest rate volatility, and other economic obstacles. The study sought to evaluate the effect of macroeconomic factors on the returns of the real estate market in Nairobi, Kenya. Specifically, the study sought to examine the effect of inflation on the returns in the real estate market in Nairobi; to evaluate the effect of GDP on the returns in the real estate market in Nairobi; to assess the effect of interest rates on the returns in the real estate market in Nairobi and to establish the effect of money supply on the returns in the real estate market in Nairobi. The study included household income as a moderator variable. The study was anchored on the modern portfolio theory as well as the arbitrage pricing theory. A descriptive research design was used in the study. Secondary data from the Central Bank of Kenya, KNBS and Hass Consult Index was used. The study found that interest rate and property rates were positively and significantly related (β=0.692, P=0.007) and that money supply has a positive and significant effect on property prices (β=0.321, P=0.000). Also, economic growth (GDP) was positively and significantly related to property prices (β=0.326, P=0.015). In addition, inflation was found to have a positive and significant effect on property prices in Nairobi (β=0.298, P=0.004). Finally, household income was positively and significantly associated with property prices in Nairobi (β=0.285, P=0.008). The research study concluded that inflation, GDP, interest rates, money supply and household income all have a positive and significant effect on the returns of the real estate market in Nairobi.
A Research Project Submitted in partial fulfillment of the requirements for the Degree of Bachelor of Commerce (Finance) at Strathmore University
Keywords: Real Estate Sector; Real Estate Management